Unveiling the assembly of neutral marine polysaccharides into electrostatic-driven layer-by-layer bioassemblies by chemical functionalization - Monteiro, Luís P. G. (2023)
Marine-origin polysaccharides, in particular cationic and anionic ones, have been widely explored as building blocks in fully natural or hybrid electrostatic-driven Layer-by-Layer (LbL) assemblies for bioapplications. However, the low chemical versatility imparted by neutral polysaccharides has been limiting their assembly into LbL biodevices, despite their wide availability in sources such as the marine environment, easy functionality, and very appealing features for addressing multiple biomedical and biotechnological applications. In this work, we report the chemical functionalization of laminarin (LAM) and pullulan (PUL) marine polysaccharides with peptides bearing either six lysine (K6) or aspartic acid (D6) amino acids via Cu(I)-catalyzed azide-alkyne cycloaddition to synthesize positively and negatively charged polysaccharide-peptide conjugates. The successful conjugation of the peptides into the polysaccharide's backbone was confirmed by proton nuclear magnetic resonance and attenuated total reflectance Fourier-transform infrared spectroscopy, and the positive and negative charges of the LAM-K6/PUL-K6 and LAM-D6/PUL-D6 conjugates, respectively, were assessed by zeta-potential measurements. The electrostatic-driven LbL build-up of either the LAM-D6/LAM-K6 or PUL-D6/PUL-K6 multilayered thin film was monitored in situ by quartz crystal microbalance with dissipation monitoring, revealing the successful multilayered film growth and the enhanced stability of the PUL-based film. The construction of the PUL-peptide multilayered thin film was also assessed by scanning electron microscopy and its biocompatibility was demonstrated in vitro towards L929 mouse fibroblasts. The herein proposed approach could enable the inclusion of virtually any kind of small molecules in the multilayered assemblies, including bioactive moieties, and be translated into more convoluted structures of any size and geometry, thus extending the usefulness of neutral polysaccharides and opening new avenues in the biomedical field, including in controlled drug/therapeutics delivery, tissue engineering, and regenerative medicine strategies.